Prevalence of specifics herpes simplex virus-2 antibodies and associated factors in university population. - Gaviria Nuñez, Angela (2020)
OBJECTIVE: To estimate the seroprevalence and identify factors associated with herpes simplex virus type 2 infection in populations young. MATERIALS AND METHODS: Transversal study in young of the University of Medellin. A representative sample of 233 individuals, previous informed consent was interviewed about socio-demographic aspects, smoking, and sexual activity. Antibodies to Herpes simplex virus type 2 were determined by a specific type immunoenzymatic technique (ELISA). We performed bivariate relation between infection with herpes simplex virus type 2 and studied factors. RESULTS: The seroprevalence of infection with herpes simplex virus type 2 in the general population was 7.3%. In women were 6.1% and man 11.5%. No found associations with antibodies to herpes simplex virus type 2 with condom use, the age, lifetime number of sexual partners, and the use of the tobacco. CONCLUSIONS: The overall seroprevalence of young in Medellin, Colombia is less than the reported in other Latin American countries however given the existence of risk factors for infection in this population, it is recommended programs emphasize sexual and reproductive health.